Addressing antimicrobial resistance by improving access and quality of care-A review of the literature from East Africa. - Kathrin Loosli; Alicia Davis; Adrian Muwonge; Tiziana Lembo (Public Library of Science (PLoS), 2021)
Universal access to healthcare, including quality medicines, is a fundamental human right but is still out of reach for many in low- and middle-income countries (LMICs). An existing framework capturing variability of access to healthcare in low-resource settings includes the 5 dimensions: availability, accessibility, affordability, adequacy, and acceptability. This framework encompasses key components, including health infrastructure and means to access it as well as service organisation, costs, and factors that influence users' satisfaction. However, in reality, the effectiveness of accessed healthcare is measured by the likelihood of a positive outcome. We therefore propose an expansion of this framework to include an additional dimension, "aspects of quality," incorporating quality, which critically influences the ability of the accessed services to generate optimal health outcomes. Within this framework, we explore literature from East Africa likely relevant to a range of LMIC contexts, mainly focusing on the provision of widely used antimicrobials such as antimalarials and antibiotics. We argue that major inadequacies exist across all 6 dimensions of access and quality of drugs and their provision. While the global focus is on curbing excessive antimicrobial use to tackle the antimicrobial resistance (AMR) crisis, major constraints around access shape patients' health-seeking decisions leading to potentially problematic practices that might exacerbate the AMR problem. We advocate for a holistic approach to tackling these inadequacies, encompassing all dimensions of access and quality of healthcare in order to improve health outcomes while simultaneously counteracting the AMR crisis.